Performance verification of a robotised fringe projection system - Khoo, Jinhao (2014)
This report highlights the potentials and capabilities of a robotised fringe projection system. Its objective is to verify the performance of such a system located in Advanced Remanufacturing and Technology Centre (ARTC), in terms of accuracy and repeatability.